Literature Review on Narrative Research from Social Sciences to Social Work: ปริทรรศน์การวิจัยแนวเรื่องเล่าทางสังคมศาสตร์สู่งานสังคมสงเคราะห์ - Tooltham, Pattanaphanu (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This article aims at reviewing narrative research methodologies brought to social sciences and social work. Narratives have also contributed from grand theory study to anecdotal study enshrined in human life experiences. Besides human life experiences have not only been their own personal experiences, but also explaining social structures and dynamics. This review article presents definitions and underpinned concepts of narrative, narrative reaching and narrative analysis. Narratives have also been brought to social work practices. Clients’ life experience is really crucial when social workers are working with until they can be resilient from their own obstacles to normal lives.